2021
DOI: 10.29333/ejmste/9573
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Pre-Service Science Teachers’ Views on Socio-Scientific Issues-Based Science Learning

Abstract: This study explores the views of Indonesian junior high school pre-service science teachers (PSTs) towards teaching based on socio-scientific issues (SSIs). Questionnaires were analyzed qualitatively and descriptively. The PSTs (N=62) acknowledged that student competencies ranging from personal to socially relevant skills as well as character formation can potentially be developed through SSI-based instruction. The PSTs mentioned several challenges which may hinder implementation of SSI-based instruction. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…When asked in the interview, the common reason given was that high school students were not considered ready to talk about complex, controversial issues. Consider the following quote: “For high school students, I don’t think they have sufficient knowledge or the skills to address an issue which is very complex such as biodiesel.” This is in line with findings by Kara and Nida et al These studies showed that many preservice teachers in Indonesia are concerned about high school students’ level of knowledge and overall ability when handling SSIs. Another reason that the PSTs in our study mentioned was that they thought that high school students needed to focus more on the science concepts.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked in the interview, the common reason given was that high school students were not considered ready to talk about complex, controversial issues. Consider the following quote: “For high school students, I don’t think they have sufficient knowledge or the skills to address an issue which is very complex such as biodiesel.” This is in line with findings by Kara and Nida et al These studies showed that many preservice teachers in Indonesia are concerned about high school students’ level of knowledge and overall ability when handling SSIs. Another reason that the PSTs in our study mentioned was that they thought that high school students needed to focus more on the science concepts.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The need for incorporating SSI-based science education in Indonesia is supported not only by theoretical and conceptual arguments, but also on an empirical base. According to the analysis of the implementation of SSI-based science education around the world by Genisa et al, it is concluded that the implementation of SSI-based science education is mostly conducted in developed countries, including the United States, Germany, Sweden, or Japan, and it is only infrequently implemented in Indonesia. , Some of the reasons for the lack of SSI-based science education in Indonesia are limited teacher knowledge about SSI-based science education and very little experience in its application. , Science teachers in Indonesia tend not to focus on the controversial nature of SSIs when they teach. Teachers, nevertheless, acknowledge that SSIs might have great potential for engaging students in science class .…”
Section: Introductionmentioning
confidence: 99%
“…While it has been implemented in a wide range of contexts in many countries, SSI-based education is still in the growing development phase in science education practice in Indonesia, with a limited number of studies having been carried out (e.g., Herlanti, Rustaman, Rohman, & Fitriani, 2012;Nida, Mustikasari, & Eilks, 2020). Science learning in secondary schools in Indonesia is taught mainly as the subjects of physics, chemistry and biology.…”
Section: Introductionmentioning
confidence: 99%
“…Promoting SSI-based learning as a useful strategy for scientific literacy in biology education in Indonesia requires well-prepared biology teachers who can be encouraged to implement SSIs and be aware of their important role in biology learning (Ekborg, Ottander, Silfver, & Simon, 2013;Forbes & Davis, 2008). However, since this strategy has been less recognized in science education practice in Indonesia, attempting its development requires addressing how Indonesian science teachers perceive their readiness to teach in this way (Nida, Rahayu, & Eilks, 2020;Nida, Mustikasari, & Eilks, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because several studies have focused on teachers' acceptance of SSIs and their views about SSIs (Akbulut & Demir, 2020;Nida et al, 2021;Parr, 2013), the current study focuses on teachers' views about the teaching of SSIs in genetics when using an inquiry approach. The argument is that whilst SSIs develop scientific literacy and bring the human aspect into science, i.e.…”
Section: Introductionmentioning
confidence: 99%